Equity in agriculture-nutrition-health research: A scoping review - Harris, Jody; Tan, Winson; Mitchell, Becky; Zayed, Dina (Oxford University Press, 2022)
Links among agriculture, nutrition, and health (ANH) are established, but the role of inequity is less understood. In this scoping review, we aimed to understand the range of ways that ANH research addresses inequity issues in low- and middle-income countries. We used PRISMA guidelines to structure our study. From an initial >26 000 studies, 243 published reports met inclusion criteria and were mapped. The number of reports addressing inequity in ANH research has increased over time from < 10 articles in 2008 to > 40 in 2018. Within equity, a majority of articles (n = 327) focused on describing how nutrition and health outcomes differ for different groups. Many (n = 134) looked at the material circumstances that shape people’s life chances. Fewer (n = 51) looked at the most basic structural determinants of (in)equity. The same aspects of equity remain the least studied in ANH research, including the intersections of equity issues shaping life chances, and inequity’s structural determinants. We suggest ways forward for this community, drawing on conceptual frameworks and theory of inequity from different disciplines.